The Implications of the Adoption of the Jewish National Law on the Palestinian Cause - Alhalalmeh, Alhareth (Dirasat: Human and Social Sciences, 2021)
This study dealt with the repercussions of approving the Jewish National Law on the Palestinian issue so that the study started from the hypothesis that the adoption of the law has a significant negative impact on the Palestinian issue and the future of statehood and from another hypothesis I have to pass the law negative effects on the future of the two-state solution and the status of the Palestinian diaspora. launching a study that asked a question about what are the effects after the approval of the law on a number of outstanding issues such as the right of return and the two-state solution and about Jerusalem, and the study used the inductive analytical method by reading and analyzing the provisions of this law and studying its effects. The study reached to a set of results that showed the negative effects on the approval of this law and that the approval of the law will lead to more violence, And that Israel demonstrated to the whole world that it is a racist state and that it does not accept the other by adopting the law. The issue of the two-state solution has been folded and prohibited the return of refugees Racist state